2013
DOI: 10.1299/kikaic.79.2635
|View full text |Cite
|
Sign up to set email alerts
|

Measurement Error of Kinetic Friction Coefficient Generated by Frictional Vibration

Abstract: To measure true values of kinetic friction coefficient in a force balance between the frictional force and spring force, an anti-vibration tribometer (AVT) has been developed. The AVT utilizes a novel principle that an angular misalignment between the two velocities (i.e., the driving velocity of one of contact surfaces and the moving velocity of the other surface) produces a positive damping effect to stabilize the equilibrium point and suppress frictional vibration autonomously. For example, when a sliding c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…6a, one can see slowly attenuating oscillations at φ = 1° (red curve) and overdamped motion without oscillations at φ = 10°. In other words, large misalignment angles suppress frictionally induced oscillations in the pulling direction [26,27]. At the same time, they can facilitate oscillations in the transverse direction as can be seen in Fig.…”
Section: Low-frequency Dynamicsmentioning
confidence: 87%
“…6a, one can see slowly attenuating oscillations at φ = 1° (red curve) and overdamped motion without oscillations at φ = 10°. In other words, large misalignment angles suppress frictionally induced oscillations in the pulling direction [26,27]. At the same time, they can facilitate oscillations in the transverse direction as can be seen in Fig.…”
Section: Low-frequency Dynamicsmentioning
confidence: 87%
“…In the fundamental theory, by observing the two velocities of the sliding surfaces in the "top view", their angular misalignment about the "yaw axis" was considered. After confirming the validity of the fundamental theory experimentally [2] and numerically [3], based on the structure of disc brakes, it was applied to a pad-on-disc-type sliding system numerically [4] and experimentally [5]. Besides, as another application format for rotational machines, the stabilizing effect of parallel misalignment in circular contacts was also shown [6].…”
Section: Introductionmentioning
confidence: 69%
“…Recently, as a promising method to stabilize mechanical systems suffering from the velocity-weakening friction, the "Yaw-Angle-Misalignment (YAM) method" has been proposed by the authors. The fundamental theory was first shown with an extended onedegree-of-freedom (1DOF) sliding system in the context of friction measurements [2]. In the fundamental theory, by observing the two velocities of the sliding surfaces in the "top view", their angular misalignment about the "yaw axis" was considered.…”
Section: Introductionmentioning
confidence: 99%
“…Substituting W into W v in equation (20), a calculation formula for the equivalent damping coefficient c eq is obtained as follows…”
Section: Effect Of and !/! N On Equivalent Damping Ratiomentioning
confidence: 99%
“…This point implies that the component of friction force can be easily controlled by changing the direction of relative velocity, even though the magnitude of friction force is hard to control. Then, Kado et al 20,21 showed that giving a slip velocity orthogonal to the direction of vibration provides a quasi-viscous damping in a 1-degree-of-freedom (1DOF) sliding system; then, it can suppress frictional vibration without any other dampers. In this method, the direction of the frictional force varies gradually and continuously when the motion of the oscillator turns over, and the damping characteristics are not significantly affected by frictional characteristics.…”
Section: Introductionmentioning
confidence: 99%